Breaking the silence of the lambs: integrating medical staff in prevention of human trafficking - Cokar, Muhtar; Ulman, Yesim Isil; Bakirci, Nadi (Acta Bioethica, 2016)
Introduction: Human trafficking, including forced prostitution, is a form of human rights violation regarding right to life and respect for human dignity. The Physician-patient relationship may serve as a process for victim identification on the basis of physicians’ responsibilities to detect human trafficking. Method: This empirical study was based on a survey among physicians who may have been in contact with foreign sex workers. Almost eighty physicians in three health facilities were selected according to their high potentiality for coming into contact with foreign sex workers as patients. 228 physicians selected to that aim. 82 of them responded to the questionnaire which was performed in order to evaluate their perception and knowledge human trafficking and their attitudes towards sex work. Results: All physicians think that some women among the sex workers are exploited, exposed to violence and coerced to work against their will (100%). Almost all of them know that it is compulsory for the healthcare professionals to inform the security forces of the women who are exploited (80.0%). Nearly half of them have given medical care to a sex worker (46.9%) and 39.0 percent have thought that it may be related to human trafficking. The ones who have informed the police of a human trafficking case are only 10 per cent. Conclusions: We think that the professional should be equipped with ethical values encompassing both a patient’s dignity and general welfare. This may include the professional’s responsibility to make an assessment as to whether the patient is a victim or a sex worker. Furthermore human trafficking in sex work and sexual health are public health issues therefore it should be covered under standards of practice and ethical codes of conduct.